Validation of Pollutant Source Identification Method Exemplified by Environmental Impact of Chornobyl Accident in ZNPP Location Area - Kozhevnikova, M.F.; Levenets, V.V.; Voyevodin, V.N. (Ядерна та радіаційна безпека, 2014)
The paper analyses environmental impact caused by the Chornobyl accident on the Zaporizhzhya NPP (ZNPP) location area. Data processing technique is proposed to detect pollution sources in the NPP region. The movement of air masses within the ZNPP 30-km zone has been analyzed. Air flow maps have been developed, and the distribution of radionuclide particles in air over the territory under study in 1986 has been determined.